Strengthening the Accessibility of Persons with Disabilities through Political Education in the 2024 General Election in Medan City - Nasution, Faiz Albar; Situmorang, Tonny Pangihutan; Fahreza, Imam; Nasution, Nabila Fahira (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The low participation of people with disabilities in elections is an issue that needs attention. Several studies have shown that people are not yet sensitive to the political rights of persons with disabilities. In addition, the lack of election accessibility for persons with disabilities is also an obstacle. Persons with disabilities are one of the large minority groups in Medan City. Therefore, this service aims to provide an understanding of strengthening the accessibility of persons with disabilities through political education in general elections in Medan City. Participatory Learning and Action methods through learning procedures that combine lecture techniques and participatory discussions to group learning are carried out in this activity. Firstly, this service activity was conducted with the Indonesian Blind Association (Pertuni) of Medan City, which includes learning about political education. Secondly, increasing the understanding of persons with disabilities about the importance of exercising their voting rights. Third, providing an understanding of political accessibility and political rights for persons with disabilities. The service results recommend that activity participants increase their understanding of the rights and obligations of citizens to vote. For the knowledge implemented in political education to run well, continuous coaching and mentoring are needed for the Indonesian Blind Association (Pertuni) in Medan City.